Contests and nominations for new words - why are they interesting and what do they show - Muhvić-Dimanovski, Vesna (Array, 2008)
The article brings an overwiew of various types of contests and similar activities in several countries, deals with criteria that are being set in these contests, and gives exampes of words that were chosen as the best ones within certain categories. The aim of the contribution is to show to what extent the so called average speakers of a language can be perceived as active participants in the evaluation of the newly coined words, what their opinion certain proposals is and can one expect that the reactions of the wider public will influence the use of new words. The article is primarily focused on the Croatian situation and the reaction of the media to the finel reults of the contest for new words published in Jezik in June 2007.